Anatomical subgroup analysis of the MERIDIAN cohort: failed commissuration. (3rd November 2017) - Griffiths, P. D.; Brackley, K.; Bradburn, M.; Connolly, D. J. A.; Gawne‐Cain, M. L.; Griffiths, D. I.; Kilby, M. D.; Mandefield, L.; Mooney, C.; Robson, S. C.; Vollmer, B.; Mason, G.
ABSTRACT: Objective: To assess the contribution of fetal magnetic resonance imaging (MRI) in fetuses of the MERIDIAN cohort diagnosed with either agenesis or hypogenesis of the corpus callosum (referred to collectively as failed commissuration) on antenatal ultrasound. Methods: This was a subgroup analysis of the MERIDIAN study of fetuses with failed commissuration (with or without ventriculomegaly) diagnosed on ultrasound in women who had MRI assessment within 2 weeks of ultrasound and for whom outcome reference data were available. The diagnostic accuracy of ultrasound and MRI was studied, as well as indicators of diagnostic confidence and effects on prognosis/clinical management. Appropriate diagnostic confidence was assessed by the score‐based weighted average method, which combines diagnostic accuracy with diagnostic confidence data. Results: In the MERIDIAN cohort, 79 fetuses were diagnosed with failed commissuration on ultrasound (55 with agenesis and 24 with hypogenesis of the corpus callosum). The diagnostic accuracy for detecting failed commissuration was 34.2% for ultrasound and 94.9% for MRI (difference, 60.7% (95% CI, 47.6–73.9%), P  < 0.0001). The diagnostic accuracy for detecting hypogenesis of the corpus callosum as a discrete entity was 8.3% for ultrasound and 87.5% for MRI, and for detecting agenesis of the corpus callosum as a distinct entity was 40.0% for ultrasound and 92.7% for MRI. There was a statistically significant improvement in 'appropriate' diagnostic confidence when using MRI as assessed by the score‐based weighted average method ( P  < 0.0001). Prognostic information given to the women changed in 36/79 (45.6%) cases after MRI and its overall effect on clinical management was 'significant', 'major' or 'decisive' in 35/79 cases (44.3%). Conclusions: Our data suggest that any woman whose fetus has failed commissuration as the only intracranial finding detected on ultrasound should have MRI examination for further evaluation. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.